2007
DOI: 10.1038/nbt1322
|View full text |Cite
|
Sign up to set email alerts
|

Embryo-specific silencing of a transporter reduces phytic acid content of maize and soybean seeds

Abstract: Phytic acid in cereal grains and oilseeds is poorly digested by monogastric animals and negatively affects animal nutrition and the environment. However, breeding programs involving mutants with less phytic acid and more inorganic phosphate (P(i)) have been frustrated by undesirable agronomic characteristics associated with the phytic acid-reducing mutations. We show that maize lpa1 mutants are defective in a multidrug resistance-associated protein (MRP) ATP-binding cassette (ABC) transporter that is expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
299
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(314 citation statements)
references
References 42 publications
9
299
1
5
Order By: Relevance
“…The total seed phosphorus in these mutants was unaffected, while reduction in phytic acid resulted in corresponding increases in inorganic P in the seed. However, lp mutants, in general, had reduced germination and seedling development and yielded low compared to WT (Meis et al 2003;Pilu et al 2003;Oltmans et al 2005;Shi et al 2007), with some exception in barley (Bregitzer and Raboy 2006), soybean (Yuan et al 2007), and common bean (Campion et al 2009). Badone et al (2010) isolated a low phytic acid mutant in maize, lp1-241, with a reduction of up to 90% of phytic acid and strong pleiotropic effect on the whole plant including higher level of anthocyanins as compared to wild type either in the embryo ($3.8-fold) or in the aleurone layer ($0.3-fold).…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
See 1 more Smart Citation
“…The total seed phosphorus in these mutants was unaffected, while reduction in phytic acid resulted in corresponding increases in inorganic P in the seed. However, lp mutants, in general, had reduced germination and seedling development and yielded low compared to WT (Meis et al 2003;Pilu et al 2003;Oltmans et al 2005;Shi et al 2007), with some exception in barley (Bregitzer and Raboy 2006), soybean (Yuan et al 2007), and common bean (Campion et al 2009). Badone et al (2010) isolated a low phytic acid mutant in maize, lp1-241, with a reduction of up to 90% of phytic acid and strong pleiotropic effect on the whole plant including higher level of anthocyanins as compared to wild type either in the embryo ($3.8-fold) or in the aleurone layer ($0.3-fold).…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
“…For example, transgenic maize containing phyA2 gene showed a very high phytase activity (1791-2502 Unit kg À1 seed) and reduced phytic acid compared to WT (Chen et al 2008). Meanwhile, a MRP ATP-binding cassette transporter is highly expressed in embryo, and by silencing expression of this transporter, Shi et al (2007) produced transgenic maize low in seed phytate but high in Pi. The rice Ins(3)P 1 synthase gene (RINO1) is highly expressed in developing seed embryos and in the aleurone layer, where phytic acid is synthesized and stored.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…Although biochemical, mapping and gene expression data suggest the mips1s gene as a candidate for lpa1 mutation in maize (Raboy et al, 2000;Pilu et al, 2003;Shukla et al, 2004;Pilu et al, 2005), recent transposon mutagenesis experiments found that a novel gene designated ZmMRP4 (accession number EF86878), coding a multidrug resistance-associated-protein (MRP) mapping near the mips1s sequence, is the actual responsible gene for lpa1 mutation (Shi et al, 2007). MRP proteins represent a subfamily of ATP-binding cassette transmembrane transporters widespread in all eukaryotes, which in plants are involved in several functions, such as xenobiotic detoxification, organic ions transport, oxidative stress tolerance (Swarbreck et al, 2003) and even transpiration control (Klein et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches are being investigated: 1) modulation of the expression of myo-inositol kinase (MIK) (Shi et al, 2008;Kruger et al, 2012a), which is responsible for myo-inositol phosphorylation (Shi et al, 2005); and 2) modulation of phytate synthesis utilising multidrug resistance-associated protein (MRP) nucleotides to modulate expression of MRPs (Shi et al, 2011;Kruger et al, 2013). Mutations in the MRP transporter gene 5 (a member of the ATP-Binding Cassette (ABC) transporter gene family) which silence expression of this transporter, have been found to dramatically reduce phytate in cereal grains and legume grains (Shi et al, 2007;Xu et al, 2009; reviewed by Raboy 2009). Importantly, it has been found that in maize, the resulting low phytic acid-high inorganic phosphate seeds germinated normally and did not have a significant reduction in seed weight (Shi et al, 2007).…”
Section: Antinutrients Phytatementioning
confidence: 99%
“…Mutations in the MRP transporter gene 5 (a member of the ATP-Binding Cassette (ABC) transporter gene family) which silence expression of this transporter, have been found to dramatically reduce phytate in cereal grains and legume grains (Shi et al, 2007;Xu et al, 2009; reviewed by Raboy 2009). Importantly, it has been found that in maize, the resulting low phytic acid-high inorganic phosphate seeds germinated normally and did not have a significant reduction in seed weight (Shi et al, 2007).…”
Section: Antinutrients Phytatementioning
confidence: 99%